1998
DOI: 10.1002/(sici)1096-9101(1998)23:3<128::aid-lsm2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Saline flush during excimer laser angioplasty: Short and long term effects in the rabbit femoral artery

Abstract: Background and Objective: In this study, the effect of flushing saline on arterial wall damage (medial ruptures and necrosis), intimal hyperplasia, and arterial remodeling was determined. During excimer laser coronary angioplasty saline is flushed to reduce the size of explosive water vapor bubbles formed by intraluminal delivery of excimer laser pulses in blood. Methods In the femoral artery of the rabbit, 600 excimer laser pulses (308 nm, 50 mJ/mm2 per pulse, 20 Hz) were delivered coaxially over a length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The segments were cut in duplicate 5 μm cross sections and were stained with hematoxylin and eosin, elastin van Gieson (EvG) and picro‐sirius red (PSR). Proliferation was detected with the monoclonal MIB‐1 antibody as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…The segments were cut in duplicate 5 μm cross sections and were stained with hematoxylin and eosin, elastin van Gieson (EvG) and picro‐sirius red (PSR). Proliferation was detected with the monoclonal MIB‐1 antibody as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Several strategies have been proposed to minimize the negative collateral effects generated by cavitation. Van Leeuwen et al (1998) also investigated the effect of flushing saline during pulse delivery on the arterial wall damage. Oberhoff et al (1992) suggested to divide the energy of one XeCl laser pulse both spatially and in time into eight smaller pulses (pulse multiplexing) which diminishes the area radiated with each pulse and thus cavitation effects.…”
Section: Collateral Effects Induced By Cavitationmentioning
confidence: 99%
“…The lifetime of PTMB is proportional to its maximal diameter, which can be controlled by varying laser pulse fluence. The laser pulse can be delivered through an optical fiber catheter [22,23,35,36] and through optically transparent media between the catheter tip and the plaque (such as saline buffer) because blood cells would scatter and decrease the optical energy of the pump laser pulse. As the PTMBs remove a plaque tissue, the process should be repeated until the re-canalization is achieved (Fig.…”
Section: Vessel Re-canalization With Ptmbmentioning
confidence: 99%
“…Laser-induced bubbles were previously employed in the laser angioplasty [22][23][24][25][26][27]; nevertheless, the mechanism of generation of the bubbles (using the tissues as optical absorber and relatively long laser pulses) resulted in accompanying heating of the collateral normal tissues, relatively big size of the laser-induced bubbles (millimeters) and, consequently, in a thermal and mechanical damage to artery walls [16,17,28,29]. Compared to cardiovascular laser-induced bubbles [16,17,28,29], application of light-absorbing micro-and nanoparticles provided significant reduction in bubble size and in laser threshold energies, required for the generation of such bubbles [30][31][32].…”
Section: Introductionmentioning
confidence: 99%